(untitled) (The Strategic Review for Southern Africa, 2021)
The paper argues for the need to look beyond norms in accounting for the Southern African Development Community’s (SADC) noncommittal approach to crisis management in Zimbabwe as from the year 2000 onwards. To justify this need, the paper highlights some notable limitations in the dominant normative explanations for SADC’s noncommittal approach to Zimbabwe. The paper posits that despite their popularity, norms do not account for SADC’s inconsistent approach to crisis management. Norms therefore, provide a partial and incomplete explanation for SADC’s noncommittal approach to Zimbabwe. The paper concludes that the key factors shaping SADC’s noncommittal approach to Zimbabwe go beyond just norms to include regional power dynamics in SADC. Therefore, this paper recommends extending debate on SADC’s approach to Zimbabwe beyond the currently dominant issue of norms. Key words: Norms, crisis-management, non-interference, SADC, Zimbabwe